Yoga dalam Mengurangi Low Back Pain pada Ibu Hamil Trimester III - Islah Wahyuni (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
Pregnancy is something that women experience in all forms that can be experienced during pregnancy. Back and waist pain is an inconvenience that is often encountered during the third trimester of pregnancy. Today, Prenatal yoga is known to help reduce the complaints experienced by mothers. This study aims to identify prenatal yoga against low back pain in third trimester pregnant women. Data were obtained by giving 4 weeks of prenatal yoga practice and assessing the response of Visual analog scale-pain (VAS-P) and satisfaction before and after exercise. The data collection design used a qualitative descriptive study of 12 pregnant women. Data processing used paired t-test. The results showed that the average VAS-P before 5.58 and before treatment was 3.42, the difference in the VAS-P value before and after treathment was 2.17, based on the satisfaction of pregnant women the decrease in low back pain after prenatal yoga practice was 100% very satisfied, there was differences in the level of low back pain before and after prenatal yoga practice in pregnant women (p-value .000). It is hoped that pregnant women can carry out prenatal yoga exercises with midwife assistance and routine exercises at home during this pregnancy.